Pengaruh Non-Performing Financing, Financing to Deposit Ratio dan Capital Adequacy Ratio Terhadap Pembiayaan Mudharabah Musyarakah pada PT. Bank Syariah Bukopin - Haris Al Amin; Reynold Herwinsyah; Syawal Harianto; Triyanda Putri Kharisma (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This research aims to determine whether or not the influence of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR) on Mudharabah and Musyarakah financing to PT Bank Syariah Bukopin in Indonesia, both simultaneously and partially. This study uses secondary data in the form of quarterly reports and in the quantitative form obtained from the official site with time-series data, namely in the period 2009-2018. The statistical test used is by multiple linear regression analysis using SPSS version 17.0 software by considering the Classical Assumption Test, which is Normality Test, Autocorrelation Test, Heteroscedasticity Test, and Multicollinearity Test. The results of the study state that Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR) simultaneously have a positive and significant effect on Mudharabah and Musyarakah financing. Non-Performing Financing (NPF) partially has a positive and significant effect on Mudharabah and Musyarakah financing because the significance value is smaller than 0.05, which is equal to 0.009. while the Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) partially have a negative and significant effect on Mudharabah and Musyarakah financing. The coefficient of determination (R2) in this study is 52.4%, this indicates that the variables of influence of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR) can explain Mudharabah and Musyarakah financing variables of 52.4% and the remaining 47.6% is explained by other variables outside the research variable.